Half truths : God helps those who help themselves and other things the Bible doesn't say - Hamilton, Adam, 1964- (Abingdon Press, 2016)
They are simple phrases. They sound Christian -- like something you might find in the Bible. We've all heard these words. Maybe we've said them. They capture some element of truth, yet they miss the point in important ways. Join Adam Hamilton in searching for the whole truth by comparing common Christian clichés to the message and ministry of Jesus. The clichés include : Everything happens for a reason ; God helps those who help themselves ; God won't give you more than you can handle ; God said it, I believe it, that settles it ; Love the sinner, hate the sin.